Peran Perangkat Desa Dalam Akuntanbilitas Pengelolaan Keuangan Desa: Studi Pada Desa Karangsari Kecamatan Sukodono - Neny Tri Indrianasari (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2017)
Research aims to understand the role of device village in Karangsari Village Sukodono District in accountability of financial management village are sufficient. Technique data collection used in this research was using interviews, documentation, and the questionnaire. Sample in this research consisted of 10 people involved in accountability of financial management village. This research uses the method descriptive analysis quantitative. The results of research conducted shows that device village is quite a role in the management village finance and in the entire management of the financial management village in accordance with Permendagri no. 113 2014. Accountability the management of the starting from the design, village officials do meetings to discuss the medium term development plan village. In the village finance funding filing village finance is accompanied by the budget costs and village treasurer to pay according to a plan budget approved by the village. In the administration of cash receipts and disbursements made by the village treasurer conducted using bookkeeping included into the general ledger, tax aide book and bank book. Village financial reporting on funds used in one year. In the accountability of the village apparatus accountable to the Report on the Realization of the Implementation of the Village Revenue and Expenditure Budget